Outbreak of Norovirus GII.P17-GII.17 in the Canadian Province of Nova Scotia - Jason J. LeBlanc; Janice Pettipas; Daniel Gaston; Robin Taylor; Todd F. Hatchette; Tim F. Booth; Russell Mandes; Andrew McDermid; Elsie Grudeski (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Norovirus is the leading cause of viral gastroenteritis, with GII.4 being the most common circulating genotype. Recently, outbreaks in China revealed that norovirus GII.17 GII.P17 had become predominant. Objective. This study aimed to characterize the distribution of norovirus genotypes circulating in Nova Scotia. Methods. Stool specimens were collected from gastrointestinal outbreaks in Nova Scotia between Jan 2014 and June 2015 and subjected to real-time RT-PCR. Norovirus-positive specimens were referred to the National Microbiology Laboratory for sequence-based genotyping. Results. The first norovirus GII.P17-GII.17 outbreak in Canada was identified, but no widespread activity was observed in Nova Scotia. Discussion. It is unknown whether GII.P17-GII.17 is more widespread in Canada since contributions to Canadian surveillance are too sparse to effectively monitor the epidemiology of emerging norovirus genotypes. Conclusions. Presence of norovirus GII.17:P17 in Canada highlights the need for more systematic surveillance to ensure that molecular targets used for laboratory detection are effective and help understand norovirus evolution, epidemiology, and pathogenesis.